THE ROLE OF INTERNATIONAL HOTEL BUSINESS IN GLOBAL ECONOMY AND FEATURES OF DEVELOPMENT - Doniyor Tursunov, (TADQIQOTLAR, 2025)
Abstract. The international hotel business plays a significant role in shaping the global  economy  by  facilitating  tourism,  creating  employment  opportunities,  and fostering cross-cultural exchange. As one of the most dynamic sectors of the service industry, hotels contribute to GDP growth, attract foreign investment, and stimulate the development of related industries such as transportation, catering, and entertainment. In recent decades, globalization has accelerated the expansion of international hotel chains,  enabling  standardized  services,  technological  innovation,  and  sustainable practices  across  diverse  markets.  This  study  analyzes  the  economic  impact  of  the international hotel business,   highlighting its contribution to national competitiveness and  regional  development.  It  also  examines  key  features  of  the  sector’s  evolution, including digital transformation, ecological responsibility, and the growing demand for personalized  guest  experiences.  The  findings  suggest  that  the  international  hotel industry  is  not  only  a  driver  of  economic  growth  but  also  a  catalyst  for  cultural integration and sustainable development in the global economy.